2022
DOI: 10.1002/mnfr.202101122
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Sesamol on Deep‐Frying Oil‐Induced Liver Metabolism Disorders by Altering Gut Microbiota and Protecting Gut Barrier Integrity

Abstract: Scope The total polar components (TPC) in the edible oil are produced during the frying process, and excessive intake of TPC may lead to metabolic disorders. This study aims to investigate the preventive effects of sesamol, a functional component from sesame, on suppressing TPC production, and on the deep‐frying oil (DFO)‐induced liver lipid metabolism disorders and gut homeostasis disruption. Methods and results Sesamol addition (0.2 mg mL−1) improves the quality of the soybean oil by reducing the production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…The pooled mean difference of five studies for the effects of deep‐frying oil intake on body weight were significantly reduced [weighted mean difference (WMD) =−2.54; 95% CI: −4.24, −0.84, P < 0.05]; however, heterogeneity existed between studies (Figure S2; Iablokov et al., 2010; Zhou et al., 2016; Qu et al., 2018; Rayhan et al., 2020; Wang et al., 2022). Given the significant heterogeneity in the meta‐analysis of all the included studies, subgroup analyses were performed to better understand the heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…The pooled mean difference of five studies for the effects of deep‐frying oil intake on body weight were significantly reduced [weighted mean difference (WMD) =−2.54; 95% CI: −4.24, −0.84, P < 0.05]; however, heterogeneity existed between studies (Figure S2; Iablokov et al., 2010; Zhou et al., 2016; Qu et al., 2018; Rayhan et al., 2020; Wang et al., 2022). Given the significant heterogeneity in the meta‐analysis of all the included studies, subgroup analyses were performed to better understand the heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study and other studies have indicated that thermally processed oils had different effects on gut microbiota compared with fresh oil (Liu et al ., 2014; Koo & Nyachoti, 2019; Ruan et al ., 2021; Wang et al ., 2022). The current study revealed the wide discrepancies in gut microbiota between heated and fresh perilla oil, or heated and fresh sunflower oil, suggests the thermally processing have complicated influence on the health benefits of vegetable oils rich in PUFAs.…”
Section: Discussionmentioning
confidence: 99%
“…Thermally processing of oils, deep frying etc ., induces thermal oxidation and polymerisation of oils, produces trans fatty acids and peroxidised compounds, which may impair the glucose and lipid metabolism in animals and humans (Choe & Min, 2007; Chiang et al ., 2011; Ringseis & Eder, 2011; Ringseis et al ., 2016). Particularly, frying oils modified the gut microbiome, and reduce relative abundance of Prevotella , Bifidobacterium and Akkermansia (Zhou et al ., 2016; Wang et al ., 2022). However, these published works focused on the effects of heated oils rich in omega‐6 PUFAs, and in the current study, we compared the different effects of heated or unheated sunflower oil which is rich in omega‐6 linoleic acid, and perilla oil which is rich in omega‐3 ALA, on gut microbiota in rats, and found thermally processing have a critical influence on prebiotic effects of PUFAs.…”
Section: Introductionmentioning
confidence: 99%
“…The “gut–liver” axis has been proposed to explain hepatic lipid metabolism disorder, suggesting that liver dysfunction leads to impairment of the intestinal barrier . The portal system allows bacteria and endotoxins from the digestive tract to enter the liver, resulting in liver damage . According to an increasing number of clinical reports and animal research, hepatic dyslipidemia has been tightly related to the equilibrium and composition of the gut microflora.…”
Section: Introductionmentioning
confidence: 99%
“…14 The portal system allows bacteria and endotoxins from the digestive tract to enter the liver, resulting in liver damage. 15 According to an increasing number of clinical reports and animal research, hepatic dyslipidemia has been tightly related to the equilibrium and composition of the gut microflora. Previous studies have suggested that disordered lipid metabolism induced by HFD breaks the balance between Firmicutes and Bacteroides in the gut.…”
Section: Introductionmentioning
confidence: 99%